Psychological Analysis of Professionally Significant Values of Future Pedagogues - Potapchuk, Lyudmyla; Kordunova, Nataliya (Psychological Prospects Journal, 2016)
The article represents theoretical and empirical analysis of professionally significant values of students that appear for future pedagogue as strategic objectives of its activity. In the work scientific approaches to understanding the concept of “value” and “value orientations” are analyzed. The connection of such concepts as “personality”, “life position”, and “professional activity” is determined. It is indicated that values − is complex social psychological phenomenon that characterizes orientation and content of active personality. Being based on values, personality determines its life position, affecting the world outlook in general. It is shown that value orientations is significant component of personality structure, they are likely to summarize the whole life experience, accumulated in its individual development. The program of empirical research has been developed. The group of values that have high significance level for future profession obtaining is determined. It is empirically determined that professionally significant values continue to be formed at the current age period; they are not completed yet and require correction during further changes. The attention is focused on the necessity for the obtained results further studying for creating training session’s programs of student’s values formation, according to their individual peculiarities. Keywords: personality, values, value orientations, professional values, professional sphere, professional activity.